Linguistic Validation of Indonesian Version of the Audit of Diabetes-Dependent Quality of Life Questionnaire - Putri Amelia Rooswita; Yunita Nita; Elida Zairina; Gesnita Nugraheni; Libriansyah Libriansyah (Universitas Airlangga, 2021)
Background: One of the impacts experienced by diabetes mellitus patients is a decrease in their quality of life. The Audit of Diabetes-Dependent Quality of Life (ADDQoL) is a widely used individualized diabetes-specific quality of life measure. However, there was no version available in the Indonesian language. Objective: This study is aimed to undertake linguistic validation, including a cultural adaptation of the ADDQoL questionnaire into the Indonesian language. Method: The original developer granted permission to use and modify the questionnaire. The international linguistic validation procedure developed by the Mapi Research Institute was used. There were six steps involved: forward translation, reconciliation, back translation, expert panel review by a psychologist and clinician, cognitive debriefing with diabetes patients, and proofreading. Result: Problems that arose during the linguistic validation process were resolved by finding conceptually equivalent alternatives and changing sentence structures to achieve equivalence in language, concept, and culture with the original version of the ADDQoL. The developer's team reviewed and discussed all actions taken. Cognitive debriefing interviews with five respondents showed that the ADDQoL questionnaire was simple to understand. Conclusion: The Indonesian version of the ADDQoL is linguistically and culturally validated. Further studies are needed to confirm the structure and reliability of the Indonesian ADDQoL.